Possible Insights into the Use of Silver Nanoparticles in Targeting SARS-CoV-2 (COVID-19) - Ghosh, Abhinav Raj; AN, Bhooshitha; HM, Chandan; Krishna, KL (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: The aims of this review are to assess the anti-viral and targeting strategies using nano materials and the possibility of using Silver nanoparticles for combating the SARS-CoV-2. Background: The novel Coronavirus (SARS-CoV-2) has become a global pandemic and has spread rapidly worldwide. Researchers have successfully identified the molecular structure of the novel coronavirus however significant success has not yet been observed with the therapies currently in clinical trials and exhaustive studies are yet to be carried out in the long road to discovery of a vaccine or a possible cure. Another hurdle associated with the discovery of a cure is the mutation of this virus which may occur at any point in time. Hypothesis: Previous studies have identified a wide number of strains of Coronaviruses with differences in virulent properties. Silver nanoparticles have been used extensively in anti-viral research with promising results in-vitro. However, it has not yet been tested for the same in clinical subjects. It has also been tested on two variants of coronavirus in-vitro with significant data to understand the pathogenesis and which may be implemented in further research possibly in other variants of coronavirus. Another interesting targeting approach would be to test the effect of Silver Nanoparticles on TNF-α as well as Interleukins in SARS-CoV-2 patients. Conclusion: Sufficient evidence is required for its therapeutic potential and it still has to go a long way in SARS-CoV-2 research.
Keywords: SARS-CoV-2; Pandemic; Immunomodulation; Silver nanoparticles; In-vitro